ALS-like pathology diminishes swelling of spinal astrocytes in the SOD1 animal model - Filipi, Tereza; Tureckova, Jana; Vanatko, Ondrej; Chmelova, Martina; Kubiskova, Monika; Sirotova, Natalia; Matejkova, Stanislava; Vargova, Lydia; Anderova, Miroslava (Frontiers in Cellular Neuroscience, 2024)
Astrocytes are crucial for the functioning of the nervous system as they maintain the ion homeostasis via volume regulation. Pathological states, such as Amyotrophic lateral sclerosis (ALS), affect astrocytes and might even cause a loss of such functions. In this study, we examined astrocytic swelling/volume recovery in both the brain and spinal cord of the SOD1 animal model to determine the level of their impairment caused by the ALS-like pathology. Astrocyte volume changes were measured in acute brain or spinal cord slices during and after exposure to hyperkalemia. We then compared the results with alterations of extracellular space (ECS) diffusion parameters, morphological changes, expression of the Kir4.1 channel and the potassium concentration measured in the cerebrospinal fluid, to further disclose the link between potassium and astrocytes in the ALS-like pathology. Morphological analysis revealed astrogliosis in both the motor cortex and the ventral horns of the SOD1 spinal cord. The activated morphology of SOD1 spinal astrocytes was associated with the results from volume measurements, which showed decreased swelling of these cells during hyperkalemia. Furthermore, we observed lower shrinkage of ECS in the SOD1 spinal ventral horns. Immunohistochemical analysis then confirmed decreased expression of the Kir4.1 channel in the SOD1 spinal cord, which corresponded with the diminished volume regulation. Despite astrogliosis, cortical astrocytes in SOD1 mice did not show alterations in swelling nor changes in Kir4.1 expression, and we did not identify significant changes in ECS parameters. Moreover, the potassium level in the cerebrospinal fluid did not deviate from the physiological concentration. The results we obtained thus suggest that ALS-like pathology causes impaired potassium uptake associated with Kir4.1 downregulation in the spinal astrocytes, but based on our data from the cortex, the functional impairment seems to be independent of the morphological state.